Central obesity is detrimental to anti-inflammatory, phenotype, and exhaustion markers in mononuclear cells - A cross-sectional study - Olean-Oliveira, Tiago [UNESP]; Padilha, Camila S. [UNESP]; Figueiredo, Caique [UNESP]; Dorneles, Gilson Pires; Marmett, Bruna; Peres, Alessandra; Romão, Pedro; Abílio de Souza Teixeira, Alexandre; Jabur Ribeiro, José Procópio [UNESP]; Dos Santos, Vanessa Ribeiro [UNESP]; Olean-Oliveira, André [UNESP]; Teixeira, Marcos F.S. [UNESP]; et al. (Elsevier, 2023)
Objective: To investigate the role of central obesity on immunometabolic response in peripheral blood mononuclear cells (PBMCs) from normal weight and overweight/obese young men. Methods: Eighteen individuals were classified as normal weight (NW; n = 9 - age: 25 ± 5 and BMI: 21.4 ± 1.7) and overweight/obese (OW; n = 9 - age: 29 ± 7 and BMI: 29.2 ± 2.7). The body composition was evaluated by dual-energy x-ray absorptiometry (DXA), waist circumference, and visceral and subcutaneous fat depots by ultrasound. Physical activity levels, metabolic parameters, immune phenotypic characterization, cytokine production by lipopolysaccharide (LPS) -stimulated whole blood cells and LPS or phorbol 12-myristate 13-acetate (PMA)-stimulated PBMC, and mitochondrial respiration in PBMCs were evaluated. Expression of AMP-activated protein kinase (AMPK), peroxisome proliferator-activated receptor gamma (PPAR-γ), nuclear factor-kappa B (NF-κB), toll-like receptor 4 (TLR-4), hypoxia-inducible factor-1 alpha (HIF-1α), and adrenergic receptor beta 1 and 2 (AR-β1 and β2) genes were evaluated in cultured PBMC using quantitative real-time polymerase chain reaction (qRT-PCR). Results: Individuals with overweight/obese (OW) presented higher glucose (P = 0.009) and leptin (P = 0.010) than individuals with normal weight (NW). PBMCs of OW under stimulation with LPS presented a lower production of interleukin-10 (IL-10) (P = 0.011) and macrophage inflammatory protein-1alpha (MIP-1α) (P = 0.048) than NW. Mitochondrial respiration rates were not different between NW and OW subjects. Cultured PBMCs in LPS-stimulated condition indicated higher gene expression of AR-β2 in OW, while PMA-stimulated PBMCs presented lower expression of AMPK (P = 0.002) and higher expression of NF-κB (P=<0.0001) than NW. OW presented higher numbers of CD3+CD4+ T cells (P = 0.009) and higher expression of programmed cell death protein 1 (PD-1) in CD8+ T cells (P = 0.001) than NW. Conclusion: Central obesity promoted reductions in interleukin 10 production response and increase in AR-β2 expressions in mitogen-stimulated PBMCs. Furthermore, central obesity altered the phenotype of PBMCs, also increasing the expression of PD-1 exhaustion markers in young adults.
Keywords: Body fat; Immune system; Immunometabolism; Physical fitness